(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
Arundinella thirunelliensis (Poaceae), a new species from the Western Ghats in Kerala, India is described and illustrated. It closely resembles A. nepalensis but differs by being a rheophyte with large culms, glabrous culm nodes, leaf sheath and peduncles, effuse panicles with highly branched drooping branches, large, 3-nerved, deeply bifid smooth lemma with short twisted column of awn, and the lower glume distinctly shorter than the lower lemma. DOI: http://dx.doi.org/10.3329/bjpt.v21i2.21354 Bangladesh J. Plant Taxon. 21(2): 153-157, 2014 (December)